Design of event‐triggered networked control systems via specific triggering quantizer. (17th August 2020) - Chen, Ziran; Zhang, Baoyong; Li, Yongmin; Ma, Qian; Zhang, Yijun
Summary: Based on a new triggering quantizer, this article studies the design of networked control systems with limited bandwidth. The design algorithm is described by the program flow diagram, which implements the functions of sampling, quantization and triggering strategy. By using a specific random variable, the effects of networked issues are captured, so as to process the design procedure. Because of the nonlinearities induced by networked issues, new methods are developed to analyze the system stability. Specifically, two design methods are proposed in order to simplify the analysis and improve the performance. Finally, simulation examples are presented to verify the proposed methods.